STUDI ANALISIS KONDISI VO2MAX ATLET FUTSAL PUTRI UNIVERSITAS MAJALENGKA DIHUBUNGKAN DENGAN PRESTASI - Indra Yogi (Jurnal Educatio, 2017)
AbstractThrough futsal, young people gain many benefits, especially in terms of good physical, mental and social growth. The goal of people doing futsal is basically the same, namely to get pleasure, get physical fitness and to achieve optimal performance. This research is a type of descriptive study, which aims to determine the condition of VO2Max futsal athletes of the University of Majalengka and is associated with futsal achievements as they are without giving any prior treatment. The problem that occurs in female Futsal athletes at Majalengka University is the decreased level of athlete VO2Max conditions. The purpose of this study was to determine the level of VO2Max condition for female Futsal athletes regarding aerobic endurance or VO2Max. The population in this study were all female futsal athletes, amounting to 20 people. Data is collected by doing a bleep test or MFT. From the analysis of the data obtained VO2Max results. The results of the study are aerobic endurance, the average VO2max owned by Female Futsal athletes at Majalengka University is 36.35. Where 3 people (15%) are categorized as good, 11 people (55%) are categorized as moderate and 6 people (30%) are categorized as poor. Overall physical condition (VO2Max) possessed by Majalengka University Women's Futsal athletes can be categorized as Moderate (36,35).Keyword: VO2Max, futsal athletes AbstrakMelalui olahraga futsal para remaja memperoleh banyak manfaat, khususnya dalam hal pertumbuhan fisik, mental dan social yang baik. Tujuan orang melakukan permainan futsal pada dasarnya sama yaitu untuk mendapatkan kesenangan, mendapatkan kesegaran jasmani dan untuk mencapai prestasi yang optimal. Penelitian ini adalah jenis penelitian deskriptif, yang bertujuan mengetahui kondisi VO2Max atlet futsal Putri Universitas Majalengka dan dihubungkan dengan prestasi futsal seperti apa adanya tanpa memberikan perlakuan terlebih dahulu. Masalah yang terjadi pada atlet Futsal Putri Universitas Majalengka adalah menurunnya tingkat kondisi VO2Max atlet. Tujuan penelitian ini adalah untuk mengetahui tingkat kondisi VO2Max atlet Futsal Putri yang berkenaan dengan daya tahan aerobic atau VO2Max. Populasi dalam penelitian ini adalah seluruh atlet futsal Putri yang berjumlah 20 orang. Pengambilan data dilakukan dengan cara melakukan bleep tes atau MFT. Dari analisis data diperoleh hasil VO2Max. Hasil penelitian yakni  daya tahan aerobic, rata- rata  VO2max  yang  dimiliki  oleh  atlet  Futsal Putri Universitas Majalengka adalah  36,35. Dimana 3 orang (15 %) dikategorikan baik, 11orang (55%) dikategorikan sedang dan 6  orang  (30%)  dikategorikan  kurang.  Secara  keseluruhan  kondisi  fisik  (VO2Max) yang dimiliki oleh atlet Futsal Putri Universitas Majalengka dapat dikategorikan Sedang (36,35).Kata Kunci: VO2Max, Atlet futsal